Integrating electromagnetic cancer stress with immunotherapy: a therapeutic paradigm - Fuster, Mark M. (Frontiers in Oncology, 2024)
An array of published cell-based and small animal studies have demonstrated a variety of exposures of cancer cells or experimental carcinomas to electromagnetic (EM) wave platforms that are non-ionizing and non-thermal. Overall effects appear to be inhibitory, inducing cancer cell stress or death as well as inhibition in tumor growth in experimental models. A variety of physical input variables, including discrete frequencies, amplitudes, and exposure times have been tested, but drawing methodologic rationale and mechanistic conclusions across studies is challenging. Nevertheless, outputs such as tumor cytotoxicity, apoptosis, tumor membrane electroporation and leak, reactive oxygen species generation, among others are intriguing. Early EM platforms in humans are employing pulsed electric fields applied either externally or using interventional tumor contact to induce tumor cell electroporation with stromal, vascular, and immunologic sparing. It is also possible that direct or external exposures to non-thermal EM waves or pulsed magnetic fields may generate electromotive forces to engage with unique tumor cell properties, including tumor glycocalyx to induce carcinoma membrane disruption and stress, providing novel avenues to augment tumor antigen release, cross-presentation by tumor-resident immune cells, and anti-tumor immunity. Integration with existing checkpoint inhibitor strategies to boost immunotherapeutic effects in carcinomas may also emerge as a broadly effective strategy, but little has been considered or tested in this area. Unlike the use of chemo/ radiation and/or targeted therapies in cancer, EM platforms may allow for survival of tumor-associated immunologic cells, including naïve and sensitized anti-tumor T cells. Moreover, EM-induced cancer cell stress and apoptosis may potentiate endogenous tumor antigen specific anti-tumor immunity. Clinical studies examining a few of these combined EM-platform approaches are in their infancy, and a greater thrust in research (including basic, clinical, and translational work) in understanding of how EM platforms may integrate with immunotherapy will be critical in driving advances in cancer outcomes under this promising combination.